Wireless and Satellite Systems : 7th International Conference, WiSATS 2015 Bradford, UK, July 6-7, 2015, revised selected papers /: 7th International Conference, WiSATS 2015 Bradford, UK, July 6-7, 2015, revised selected papers. (2015) - Unknown
No abstract available